2014
DOI: 10.4172/2332-2543.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Marine Parasites of Omani Waters: State of knowledge

Abstract: Parasitological studies of marine fish inhabiting the Sultanate of Oman began in the late sixties of the twentieth century and continued through '82. These studies revealed a total of 154 marine parasite species belonging to ten taxonomic groups.These included myxosporeans, microsporidia, helminths, parasitic crustaceans and leeches. New species were described, some of which were categorized as harmful to public health and some were found to have an impact on the quality and marketability of their hosts. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…El-Naffar et al (1992), Kardoush (2003) also reported more than 20 species of digenetic trematode from the Emirati coasts. Some scattered studies were also recorded from other coasts, including Saudi Arabia (Bayoumy et al, 2012) and Oman (Machkevskyi et al, 2014) and Iraq (Bannai, 2002;Bannai and Essa, 2015;Bannai et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%
“…El-Naffar et al (1992), Kardoush (2003) also reported more than 20 species of digenetic trematode from the Emirati coasts. Some scattered studies were also recorded from other coasts, including Saudi Arabia (Bayoumy et al, 2012) and Oman (Machkevskyi et al, 2014) and Iraq (Bannai, 2002;Bannai and Essa, 2015;Bannai et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%